THE ANALYSIS OF AGRICULTURAL PRODUCT IN PINEAPPLE COMMODITIES IN NGANCAR DISTRICT, KEDIRI REGENCY, EAST JAVA PROVINCE - Himmati, Risdiana (Journal of Indonesian Applied Economics, 2017)
The present research has the purpose to analyze factors affecting the production of pineapple in Ngancar District, Kediri Regency, East Java Province. The research took place in Ngancar District, Kediri Regency, East Java Province, employing secondary data derived from Central Bureau of Statistics (Kediri Regency) and Agricultural Extension Agency (Ngancar District) and primary data consisted of farming production data, land area, amount of seeds, and amount of fertilizer usage, pesticide and workforce. The analysis technique used in this research was Cobb-Douglas production function. The completion upon Cobb-Douglas production functions used Ordinary Least Square (OLS) method with Eviews 9 program tool. The sampling technique employed in this research was simple random sampling method. The results demonstrate that the pineapple total production in Ngancar District is affected by land area, amount of seeds, molasses, and urea. The research concludes that pineapple production in Ngancar District is affected by all the factors of production, except the usage of pesticide and workforce.